Pengaruh Media Animasi Edukatif Terhadap Peningkatan Pemahaman Nilai Akhlak Terpuji Siswa MI - Povitasari, Povitasari (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to explore how educational animated media contributes to the comprehension and internalisation of noble moral values among students at Madrasah Ibtidaiyah (MI). The research is grounded in the phenomenon of low moral internalisation among students, despite the provision of conventional religious instruction. Employing a phenomenological qualitative approach, the study focuses on students’ subjective experiences in interpreting Islamic-themed animated content. Data were collected through semi-structured interviews, participatory observations, and document analysis involving eight students from Grades IV and V, two Islamic education teachers, and one parent, selected via purposive sampling. The findings reveal three central themes: (1) moral value internalisation through narrative visualisation, (2) emotional responses to characters and storylines, and (3) moral reflection in everyday life. Animated media was found to enhance students’ moral understanding not only cognitively, but also affectively and conatively. These findings suggest that educational animation serves as an effective medium for character development aligned with Islamic values. The study concludes by underscoring the significance of employing visual-narrative-based media in children’s moral education. Theoretically, the results support both social learning theory and multimedia learning theory within the context of character education. Practical implications include the need for teacher training and the development of contextualised, Islamic-oriented learning media. Future research is recommended to examine the long-term impact of animated media on students’ moral behaviour across diverse socio-cultural contexts.